MORTALITY FROM SUICIDE AND ALCOHOLISM, DEPENDING ON THE LEVEL OF ALCOHOL CONSUMPTION - L. A. Radkevich; A. S. Kabankin; D. A. Radkevich (Исследования и практика в медицине)
According to WHO, the world takes place every year approximately 500 000 suicides and suicide attempts of 7 million. Since 1994, Russia ranks 2nd in the world after Lithuania, in the level of suicides, and is among the countries with the linear dependence of frequency of suicides on the level of alcohol consumption.Purpose. Install a quantitative connection between the frequency of suicide with alcohol consumption and mortality from alcoholism in the world.Material and method. For studies we used the mortality coefficient (MK) from suicide and alcohol abuse (number of people/100 thousand of age standardized the population) in 159 countries according to the WHO in 2004, the average daily consumption levels of alcoholic beverages: spirits, wine and beer (g/person/day) according to the FAO (Food and Agriculture Organization of the United Nations). For data analysis we used correlation and regression methods.Results. We found significant positive correlation of mortality coefficient (MK) from suicide for men and women with consumption of alcoholic beverages (spirits, wine and beer) and mortality from alcoholism. The gender differences are revealed. Included in the regression model independent variables (levels of alcohol consumption and mortality from alcoholism) explain 66% and 52% of the variability in the frequency of suicides of men and women (dependent variables). A complete rejection of the consumption of alcohol reduces the MK from suicide of men in the world at 39.5 percent, in Russia — at 76.5%; women — 37.9%, in Russia — by 54.3%. According to the regression analysis the average daily level of consumption of strong alcohol in the world is 10.4 g (3.8 kg per year) for men, in Russia — 91.8 g (of 33.5 kg per year). The increase in the consumption of strong alcohol to 3 g per day (1 kg per year) increases the MK from suicide in men up to 10.8% (1.6 people) in the world, in Russia — 2.4% (1.6 people). The increase in the MK of alcoholism of men in the world for 1 person on 100 thousand population per year increases, the MK of suicides of men in the world by 5.8% (0.8 persons), in Russia — 1.3% (0.9 persons).Conclusions. Population studies generally confirm the existence of a positive correlation between the level of suicides (MK) and alcohol consumption, both in the world and in Russia. The frequency of suicides is more influenced by the level of consumption of strong alcohol and the MK from alcoholism. Our results support the General opinion on expediency of change of structure of consumed drinks in favor of lighter (low alcohol content), especially in Russia, which has a positive impact at the population level of suicide and alcoholism.